Humanist Islam in Indonesia Ahmad Syafii Maarif perspective - Muthoifin; Shobron, Sudarno; Ab Rahman, Suhaimi (Gyandhara International Academic Publications, 2019)
Purpose of the Study: The issue focused on this study is how is the idea of the Islamic conception in the concept of humanity and Indonesianness? Whereas the purpose of this study is to reveal the perspective of Ahmad Syafii Maarif on Islam Indonesia and the concept of humanism. Methodology: The method used is qualitative, with a historical, phenomenological, biographical, sociological, and normative approach. Results: The result from this study concluded that this is no longer the time for Muslims, who are the majority in this archipelago, to question the trilogy correlation between Islam, Indonesianness, and humanity. The three conceptions must be in the same breath and rhythm so that Islam that is thriving in Indonesia is Islam that is progressive, hospitable, open and rahmatanlil ‘alamin. Applications: This research can be used for universities, teachers, and students. Novelty/Originality: The study focused more on the description of the thinking of a figure or a person and emphasized on the process with deductive, inductive, interpretative, and comparative methods, especially on the thinking of Ahmad Syafii Maarif about the concept of Islam in the frame of Indonesianness.